2019
DOI: 10.1101/851121
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Semaphorin 3A binding to chondroitin sulfate E enhances the biological activity of the protein, and cross-links and rigidifies glycosaminoglycan matrices

Abstract: Semaphorin 3A (Sema3A) is a secreted protein that signals to cells through binding to neuropilin and plexin receptors and provides neurons with guidance cues key for axon pathfinding, and also controls cell migration in several other biological systems. Sema3A interacts with glycosaminoglycans (GAGs), an interaction that could localize the protein within tissues and involves the C-terminal domain of the protein. This domain comprises several furin cleavage sites that are processed during secretion and in previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…During adulthood, Sema3A in PNNs could stabilize existing synapses on the postsynaptic neuron. Finally, because it has been shown that Sema3A is able to rigidify CS-E-based matrices, it may cross-link PNN-GAGs, stabilizing the PNN structure [ 129 ].…”
Section: Pnns and Brain Maturationmentioning
confidence: 99%
“…During adulthood, Sema3A in PNNs could stabilize existing synapses on the postsynaptic neuron. Finally, because it has been shown that Sema3A is able to rigidify CS-E-based matrices, it may cross-link PNN-GAGs, stabilizing the PNN structure [ 129 ].…”
Section: Pnns and Brain Maturationmentioning
confidence: 99%
“…Scale bar: 2 mm (A), 5 µm (B). peptidic sequences located in the Sema3A C-terminal domain (Djerbal et al, 2019). Interestingly, one of these sequences is very similar to a sequence found in orthodenticle homeobox 2 (Otx2), which is involved in PNN formation and modulation of plasticity (Bernard and Prochiantz, 2016).…”
Section: Class 3 Semaphorins In Perineuronal Netsmentioning
confidence: 85%
“…The most common CS-GAG isoform in the adult brain are: CS-A (C-4 sulfation on GalNAc), CS-C (C-6 sulfation on GalNAc), CS-D (C-2 sulfation on GlcA and a C-6 sulfation on GalNAc), and CS–E (C-4 and C-6 sulfation on GalNAc; Sugahara and Kitagawa, 2000 ). The interaction between Sema3A and PNNs is sulfation-dependent, with Sema3A interacting preferentially to CS-E extracted from adult brain PNNs ( Dick et al, 2013 ) via two specific peptidic sequences located in the Sema3A C-terminal domain ( Djerbal et al, 2019 ). Interestingly, one of these sequences is very similar to a sequence found in orthodenticle homeobox 2 (Otx2), which is involved in PNN formation and modulation of plasticity ( Bernard and Prochiantz, 2016 ).…”
Section: Semaphorins In Adult Nervous System Physiologymentioning
confidence: 99%
See 1 more Smart Citation
“…It is possibly because of their firing properties that PV+ interneurons, concomitantly to their maturation, are enwrapped by a protective sheet of extracellular matrix, the perineuronal net (PNN) [ 14 , 15 , 16 ], which supposedly creates a protection from oxidative stress [ 17 ]. Accumulating evidence shows that SEMA3A, already expressed by these cells as they establish in the neocortex [ 18 ], binds to chondroitin sulfate proteoglycans, one of the main components of PNNs, to shape and probably stabilize the ensheathing matrix [ 19 , 20 , 21 , 22 ]. The enrichment of SEMA3A in this extracellular matrix may restrict neurite growth onto cell bodies of PV+ interneurons, which could explain why emergence of PNNs determines the closure of plasticity windows [ 23 ].…”
Section: Neuronal Maturationmentioning
confidence: 99%